The OpenBSD 4.0 crash course - Matzan, Jem (O'Reilly short cuts., 2007)
OpenBSD is a Unix-like computer operating system that is widely regarded for its excellent documentation and its fanatical focus on security. ""The OpenBSD Crash Course"" Short Cut will help you get an x86 or AMD64/EM64T server, desktop, or network appliance up and running quickly with OpenBSD. You'll learn how to install or upgrade OpenBSD on x86 and AMD64 machines, how to configure it for server or workstation use, and how to properly maintain it until the next release